2016
DOI: 10.5694/mja16.00226
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry reference values in Indigenous Australians: a systematic review

Abstract: PrefaceWhile the Council of Australian Governments (COAG) has committed to improve health outcomes and wellbeing of Indigenous 1 Australians, the principal measurable targets, for both adults and children, have been based on reductions in mortality. The adult target -to close the gap in life expectancy within a generation (25 years) -requires robust estimates of life expectancy across population groups. Life tables are essential to the calculation of these estimates.The life tables provided here have been deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
4
20
0
Order By: Relevance
“…Our study is the first to provide spirometry data of healthy Aboriginal, Torres Strait Islander and both Aboriginal and Torres Strait Islander Australian children and young adults. Unlike previous studies, our cohort consisted of >300 participants (per ethnic group) who were free of both current/chronic respiratory illnesses and smoking history. In assessing the suitability of the GLI‐2012 reference equations for use by Indigenous Australians, we found that the GLI‐2012 other/mixed equations gave the best overall fit for all lung function parameters compared to Caucasian and African‐American.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study is the first to provide spirometry data of healthy Aboriginal, Torres Strait Islander and both Aboriginal and Torres Strait Islander Australian children and young adults. Unlike previous studies, our cohort consisted of >300 participants (per ethnic group) who were free of both current/chronic respiratory illnesses and smoking history. In assessing the suitability of the GLI‐2012 reference equations for use by Indigenous Australians, we found that the GLI‐2012 other/mixed equations gave the best overall fit for all lung function parameters compared to Caucasian and African‐American.…”
Section: Discussionmentioning
confidence: 99%
“…As identified in our systematic review, there were several limitations in previously developed spirometry reference equations for Indigenous Australians that impeded their use in the clinical setting. These studies reported only Aboriginal lung function and no Torres Strait Islander or both data, and the differences in values compared to Caucasian data were greater than those typically observed in other non‐Caucasian ethnic groups .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…summarize lung function data in a large group of healthy children and young adults from Australian aboriginal and/or Torres Strait communities in Queensland and provide guidance for the use of Global Lung Function Initiative (GLI) reference equations for this population. In previous work by this team, a systematic review of available literature highlighted the lack of good‐quality studies to appropriately define the range of normal values for indigenous populations in Australia . Thus, this comprehensive prospective study of more than 1200 participants is both necessary and timely.…”
mentioning
confidence: 99%